Pledge and Review Bargaining in Environmental Agreements: Kyoto vs. Paris - Thomas Eichner; Mark Schopf (ZBW - Leibniz Information Centre for Economics, 2021)
This paper compares the Kyoto Protocol and the Paris Agreement in the dynamic game of Battaglini and Harstad (2016). The asymmetric Nash solution of this game reflects the Paris Agreement, whereas the symmetric Nash solution reflects the Kyoto Protocol. In a large set of economies, the Kyoto Protocol is Pareto superior to the Paris Agreement. Although the stable climate coalition is large in the Paris Agreement and small in the Kyoto Protocol, the emissions reductions of a single coalition country are much more pronounced in the Kyoto Protocol, so that this per-country-emissions-reduction effect outweighs the disadvantageous coalition-size effect.
Keywords: C71; F55; Q54; 330; pledge and review; emissions; investments; stable coalition